A Review of the Relationship Between Insulin and Bone Health - Sivasree Ravindran; Sok Kuan Wong; Nur-Vaizura Mohamad; Kok-Yong Chin (Biomedicines)
Insulin, a key hormone primarily involved in glucose metabolism, has emerged as a crucial modulator of bone metabolism. Increasing evidence suggests that insulin influences bone health, but its precise mechanism of action remains unestablished. This review explores the intricate relationship between insulin and bone health, as well as elucidating the mechanism of action involved. Animal models of type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) demonstrated distinct skeletal alterations, largely attributed to differences in insulin availability and associated metabolic dysfunction. Insulin deficiency in T1DM was associated with the deterioration of trabecular and cortical bone, whereas insulin resistance in T2DM primarily compromised trabecular bone quality. The route, frequency, and duration of insulin administration have been shown to influence bone-related outcomes. Studies involving insulin receptor silencing have suggested that insulin signalling is essential for normal bone development and maintenance. In humans, inconsistent findings on the effects of circulating insulin levels and insulin resistance on bone health were mainly attributed to heterogeneity in age, gender, metabolic status, study designs, population characteristics, and assessment methods. This review also highlights current knowledge gaps and underscores the need for longitudinal studies and mechanistic research. A clearer understanding of the insulin–bone axis may guide the development of targeted strategies to mitigate skeletal complications in individuals with diabetes mellitus.